Magnetic Structure and its Tectonic Implication Around Longmenshan Fault Zone Revealed by EMAG2v3 - Lei, Yu; Jiao, Liguo; Tu, Jiyao; Zhao, Junhao; Huang, Qinghua (Frontiers in Earth Science, 2022)
The formation of magnetic minerals is bound up with the tectonic evolution history, whereupon the distribution of magnetic anomalies has great meanings for regional tectonics. In this study, we use the latest global lithospheric magnetic field model EMAG2-v3, processed by various techniques including reduction to the pole (RTP), upward continuation, derivations, Euler deconvolution, estimation of total magnetization direction and Curie point depth (CPD), to unveil the tectonics around Longmenshan fault zone (LFZ). LFZ is clearly displayed as a positive and negative anomaly transition zone in RTP anomalies and acts as a magnetic basement boundary. The Sichuan Basin (SB), located on the east of LFZ, is marked by strong magnetic basement and NE-strike banded induced positive anomalies which are associated with the Neoproterozoic magmatic activity. The banded shape, absence of radial pattern of anomalies and existence of fossil subduction zone supports that the magnetic basement was formed in arc environment. The CPD in SB estimated by radial average power spectral is 30 to 51 km, which allows magnetic minerals in deep crust or even in lithospheric mantle to exhibit high magnetizations. The Songpan-Ganzi fold belt (SGFB), in contrast, located on the west of LFZ and covered by thick and low-susceptibility Triassic deposits of flysch, manifests as weak negative anomalies caused by relatively shallow CPD and widespread remanent magnetization. Significant positive anomalies appearing around the Manai and Rilonguan granitic massifs indicate strong magnetic basement beneath SGFB, which is conjectured as westward extension of the Yangtze Block at depth.